2004
DOI: 10.1099/mic.0.26860-0
|View full text |Cite
|
Sign up to set email alerts
|

Global analysis of gene expression in an rpoN mutant of Listeria monocytogenes

Abstract: The role of the alternative s 54 factor, encoded by the rpoN gene, was investigated in Listeria monocytogenes by comparing the global gene expression of the wild-type EGDe strain and an rpoN mutant. Gene expression, using whole-genome macroarrays, and protein content, using two-dimensional gel electrophoresis, were analysed. Seventy-seven genes and nine proteins, whose expression was modulated in the rpoN mutant as compared to the wild-type strain, were identified. Most of the modifications were related to car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
88
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(93 citation statements)
references
References 45 publications
5
88
0
Order By: Relevance
“…The large-scale transcriptional responses in E. coli are mediated via a limited number of global regulators (527). In enteric bacteria, global regulation of carbon metabolism involves several and transcription factors such as Crp (cyclic AMP receptor protein) (reviewed in references 76,95,96,416, and 636), Mlc (666), FruR (145,267,268,762), CsrA (carbon storage regulator) (451,742,743,752,861), and 54 (25,150,843). The activities of some of these regulators are directly affected by the PTS.…”
Section: Eiia Glc Is the Central Processing Unit Of Carbon Metabolismmentioning
confidence: 99%
“…The large-scale transcriptional responses in E. coli are mediated via a limited number of global regulators (527). In enteric bacteria, global regulation of carbon metabolism involves several and transcription factors such as Crp (cyclic AMP receptor protein) (reviewed in references 76,95,96,416, and 636), Mlc (666), FruR (145,267,268,762), CsrA (carbon storage regulator) (451,742,743,752,861), and 54 (25,150,843). The activities of some of these regulators are directly affected by the PTS.…”
Section: Eiia Glc Is the Central Processing Unit Of Carbon Metabolismmentioning
confidence: 99%
“…Transcription of lmo0027 is also enhanced in the absence of sigma-54 (Arous et al, 2004a), which is required for the transcription of lmo0096-98 and lmo2683-85. Since functional PTS Man -2 and PTS Lac -4 permeases are essential for substrate-specific activation of ManR and LacR, respectively, it is tempting to speculate that transcription of lmo0027 is either negatively controlled by active ManR and/or LacR or requires an activator that is only activated in the absence of active ManR and/or LacR.…”
Section: Discussionmentioning
confidence: 94%
“…To date there has only been one report of a potential chitinase gene possessing a conserved s 54 -dependent promoter; whole genome macroarray analysis of a Listeria monocytogenes rpoN mutant revealed that gene expression of lmo0105, a gene sequence similar to L. monocytogenes chitinase B, was different to that of the wild type (Arous et al, 2004). Transcription from s 54 -dependent promoters is tightly regulated by environmental conditions, which can be sensed through regulatory domains in the enhancer-binding protein or through interaction with regulatory proteins (Studholme and Dixon, 2003).…”
Section: Discussionmentioning
confidence: 99%